Polyphasic Analysis Reveals Potential Petroleum Hydrocarbon Degradation and Biosurfactant Production by Rare Biosphere Thermophilic Bacteria From Deception Island, an Active Antarctic Volcano - Schultz, Júnia; Argentino, Isabella Campelo Vilardi; Kallies, René; Nunes da Rocha, Ulisses; Rosado, Alexandre Soares (Frontiers in Microbiology, 2022)
Extreme temperature gradients in polar volcanoes are capable of selecting different types of extremophiles. Deception Island is a marine stratovolcano located in maritime Antarctica. The volcano has pronounced temperature gradients over very short distances, from as high as 100 °C in the fumaroles to subzero next to the glaciers. These characteristics make Deception a promising source of a variety of bioproducts for use in different biotechnological areas. In this study, we isolated thermophilic bacteria from sediments in fumaroles at two geothermal sites on Deception Island with temperatures between 50 and 100 °C, to evaluate the potential capacity of these bacteria to degrade petroleum hydrocarbons and produce biosurfactants under thermophilic conditions. We isolated 126 thermophilic bacterial strains and identified them molecularly as members of genera Geobacillus, Anoxybacillus, and Brevibacillus (all in phylum Firmicutes). Seventy-six strains grew in a culture medium supplemented with crude oil as the only carbon source, and 30 of them showed particularly good results for oil degradation. Of 50 strains tested for biosurfactant production, 13 showed good results, with an emulsification index of 50% or higher of a petroleum hydrocarbon source (crude oil and diesel), emulsification stability at 100 °C, and positive results in drop-collapse, oil spreading, and hemolytic activity tests. Four of these isolates showed great capability of degrade crude oil: FB2_38 (Geobacillus), FB3_54 (Geobacillus), FB4_88 (Anoxybacillus), and WB1_122 (Geobacillus). Genomic analysis of the oil-degrading and biosurfactant-producer strain FB4_88 identified it as Anoxybacillus flavithermus, with a high genetic and functional diversity potential for biotechnological applications. These initial culturomic and genomic data suggest that thermophilic bacteria from this Antarctic volcano have potential applications in the petroleum industry, for bioremediation in extreme environments and for microbial enhanced oil recovery (MEOR) in reservoirs. In addition, recovery of small-subunit rRNA from metagenomes of Deception Island showed that Firmicutes is not among the dominant phyla, indicating that these low-abundance microorganisms may be important for hydrocarbon degradation and biosurfactant production in the Deception Island volcanic sediments.